Social Pathology, The State, and Power: A Sociological Analysis of Community Organisation Thuggery from the Perspective of Michel Foucault - Asmoro Aji (Realism: Law Review, 2026)
This study examines the changing role of community organisations in Indonesia, where their rapid growth has been accompanied by affiliations with organised thuggery. Drawing on Michel Foucault's poststructuralist perspective, organised thuggery is understood not as an objective social pathology but as a discursive construct produced through power/knowledge relations. This study explores how the state constructs community organisations affiliated with organised thuggery as objects of security intervention through governmentality. Using a qualitative approach, the research applies Foucauldian Discourse Analysis (FDA) to analyse state regulations, government policy documents, and police telegrams issued between 2024 and 2026. The findings show that the state establishes a regime of truth by classifying community organisations into "normal" and "deviant" categories, framing intimidation, extortion, and violence as threats to public order and the investment climate. This strategy is institutionalised through the Integrated Task Force established under the Coordinating Minister for Political and Security Affairs Decree No. 61 of 2025, integrating cross-sectoral coordination, administrative oversight, law enforcement, and organisational guidance. The study concludes that controlling organised thuggery relies not only on repression but also on administrative knowledge that legitimises state intervention and normalises organisational behaviour to maintain security, public order, and a sustainable investment climate